Farmer typology formulation accounting for psychological capital: implications for on-farm entrepreneurial development. Issue 5 (4th July 2018) - Chipfupa, Unity; Wale, Edilegnaw
ABSTRACT: Understanding and accounting for the heterogeneity of small farmers is critical for informing development pathways to improve the performance of smallholder irrigation. Using multivariate analysis, this study sought to develop farmer typologies in and around irrigation schemes and used these to inform strategies for on-farm entrepreneurship development. The research uniquely integrates psychological capital in defining farmer typologies, to capture individual features of each farmer, otherwise missed by the generic sustainable livelihoods framework literature. The study affirms the need to focus on psychological capital and concludes that heterogeneity among small-scale irrigators should be accounted for in future agricultural and rural development programmes.